Bioactive silicate nanoplatelets for osteogenic differentiation of human mesenchymal stem cells - Gaharwar, Akhilesh K. (2013)
Novel silicate nanoplatelets that induce osteogenic differentiation of human mesenchymal stem cells (hMSCs) in the absence of any osteoinductive factor are reported. The presence of the silicate triggers a set of events that follows the temporal pattern of osteogenic differentiation. These findings underscore the potential applications of these silicate nanoplatelets in designing bioactive scaffolds for musculoskeletal tissue engineering.